The PhysioCam: A Novel Non-Contact Sensor to Measure Heart Rate Variability in Clinical and Field Applications - Davila, Maria I.; Lewis, Gregory F.; Porges, Stephen W. (Frontiers in Public Health, 2017)
Heart Rate Variability (HRV) is a reliable indicator of health status and a sensitive index of autonomic stress reactivity. Stress negatively affects physical and psychological wellness by decreasing cardiovascular health and reducing quality of life. Wearable sensors have made it possible to track HRV during daily activity, and recent advances in mobile technology have reduced the cost and difficulty of applying this powerful technique. Although advances have made sensors smaller and lighter, some burden on the subject remains. Chest-worn electrocardiogram (ECG) sensors provide the optimal source signal for HRV analysis, but they require obtrusive electrode or conductive material adherence. A less invasive surrogate of HRV can be derived from the arterial pulse obtained using the photoplethysmogram (PPG), but sensor placement requirements limit the application of PPG in field research. Factors including gender, age, height and weight also affect PPG-HRV level, but PPG-HRV is sufficient to track individual HRV reactions to physical and mental challenges. To overcome the limitations of contact sensors, we developed the PhysioCam, a noncontact system capable of measuring arterial pulse with sufficient precision to derive HRV during different challenges. This passive sensor uses an off the shelf digital color video camera to extract arterial pulse from the light reflected from an individual’s face. In this manuscript we validate this novel noncontact measure against criterion signals (ECG and PPG) in a controlled laboratory setting. Data from twelve subjects is presented under the following physiological conditions: rest, single deep breath and hold, and rapid breathing. The following HRV parameters were validated: Interbeat Interval (IBI), Respiratory Sinus Arrhythmia (RSA), Low Frequency HRV (LF). When testing the PhysioCam against ECG or PPG: the Bland-Altman plots for the IBIs show no systematic bias; correlation coefficients (all p values <0.05) comparing ECG to PhysioCam for IBI and LF approach 1, while RSA correlations average 0.82 across conditions. We discuss future refinements of the HRV metrics derived from the PhysioCam that will enable this technology to unobtrusively track indicators of health and wellness.